How to Distinguish Solitary Neurofibroma From Neurofibromatosis Type 1. Issue 3 (26th May 2022) - Guo, Chengrui; Zhou, Lucia; Sun, Yi; Hu, Xiaojie
Abstract : Abstract: Neurofibroma is a benign tumor originating from Schwann cells. It is diagnosed as a symptom of neurofibromatosis type 1 ( NF1 ) or solitary neurofibroma. Neurofibromatosis type 1 belongs to a class of hereditary diseases, whereas solitary neurofibroma is not. Presence of germline NF1 gene mutations can be used to distinguish the 2 conditions. However, due to false negative results in gene tests, NF1 may be misdiagnosed as solitary neurofibroma. This calls for development of more accurate diagnostic methods. The authors report 2 patients with neurofibroma who required surgery and fertility consulting. using primary cell culture and next-generation sequencing experiments, the authors found NF1 mutation in neurofibroma Schwann cells. But this mutation was not exit in peripheral blood, hence demonstrate this NF1 mutation was somatic rather than germline. These results confirmed the diagnosis of solitary neurofibroma rather than NF1 . The presented method is, therefore, suitable for fertility consultation and diagnosis of solitary neurofibroma patient.